'An act of faith' or a new 'Brown Empire'? The dismissal of India's international anti-Racism, 1945–1961. Issue 1 (2nd January 2018) - Davis, Alexander E.; Thakur, Vineet
ABSTRACT: At the inaugural UN session in 1946, an Indian-sponsored resolution was passed with a two-thirds majority against South Africa's racist treatment of Indians. India continued its activism over racism and apartheid throughout the 1950s, though the issue was increasingly seen as a painful yearly ritual. Still, Indian diplomats persisted in raising the issue every year, despite diminishing results. The British settler-colonies were particularly offended by India's campaign, as it challenged the discursive justification for their existence. They rejected what they saw as India's emotional, hypocritical, even imperialist, campaign against racism. By tracing the construction and rejection of anti-racist politics, we examine the dismissal of racism as a 'legitimate' international issue.